A Duoethnography of a Chinese Pre-Service Teacher’s Encounters with Young Learner Spelling Errors in the English Classroom - Yimei Jing; Barry Lee Reynolds (Languages, 2022)
A large body of research has indicated that young second language (L2) learners often have problems with spelling, such as letter omission and mis-ordering. To give due attention to this issue, a duoethnographic study was undertaken by two researchers from different language education backgrounds. The data were collected by way of 18 conversations (86,213-word transcription). These transcribed conversations were then reconstructed in order to accurately present the dialogue that took place between the two researchers. The conversations centered around four themes related to young Chinese learners’ English spelling issues, namely: the roles of a practicum mentor and supervisor; factors resulting in young learners’ spelling issues; the relationship between spelling and reading; implications for future teaching. The findings of this study suggest that future English teachers of young learners should implement morphological instruction, encourage students to read more, instruct students on how to make and use word cards, and explain how delayed copying should be used for spelling practice. This duoethnograpy also suggests that mentors, supervisors, and pre-service teachers should engage in duoethnographic research in order to better understand mentoring, supervision, and teaching issues, whilst also promoting professional development.